Larkspur and the grand march - "Arrigan, Mary" (Egmont Books Ltd: London, 2003)
Larkspur the lion adores opera. He has to go along when he hears it's coming to town. But with tickets so expensive, how will he get to see it? Suggested level: primary
Keywords: Opera Juvenile fiction